Impact of body mass index, gender, and smoking on thickness of free soft tissue flaps used for orofacial reconstruction. Issue 8 (October 2015) - Hakim, Samer G.; Jacobsen, Hans-Christian; Trenkle, Thomas; Sieg, Peter; Wieker, Henning
Abstract: Donor-site selection may play an important role in the reconstruction of large orofacial defects. The thickness and structure of transplanted tissue has to fit those of the recipient site to achieve a satisfactory outcome. To evaluate the thickness of free flaps that are frequently used for orofacial reconstruction and its association with body mass index (BMI), gender, and smoking, a prospective study was conducted. A total of 122 volunteers were included in the study, and their data regarding BMI, gender, and tobacco use were documented. Ultrasonography was used to evaluate the thickness of the radial and ulnar forearm flaps (RFFF and UFFF, respectively), the scapular and parascapular flaps (SF and PSF, respectively), the anterolateral thigh flap (ALT), and the free fibular flap (FF). Correlation and regression analysis were performed to assess any relationship among parameters and to investigate their effect on flap thickness. The UFFF showed the lowest thickness (0.65 ± 0.16 cm), followed by the RFFF (0.83 ± 0.20 cm). The FF showed a comparable thickness (0.82 ± 0.26 cm), followed by the SF (0.99 ± 0.13 cm) and the PSF (1 ± 0.14 cm). The ALT flap displayed the greatest thickness (1.42 ± 0.42 cm) and correlated especially with BMI and gender, whereas the UFFF was the thinnest with relatively constant values, regardless of potential influential factors.